Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10528-010-9409-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of RPE65, CRALBP, VEGF, CD68, and Tyrosinase Gene Expression in Human Retinal Pigment Epithelial Cells Cultured on Amniotic Membrane

Abstract: The retinal pigment epithelium (RPE) plays a key role in the maintenance of the normal functions of the retina. Tissue engineering using amniotic membrane as a substrate to culture RPE cells may provide a promising new strategy to replace damaged RPE. We established a method of culturing RPE cells over the amniotic membrane as a support for their growth and transplantation. The transcription of specific genes involved in cellular function of native RPE, including RPE65, CRALBP, VEGF, CD68, and tyrosinase, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Additionally, we have included multiple RPE-specific markers (e.g., bestrophin) in our 708 709 710 711 712 713 714 715 716 717 718 719 720 721 722 723 724 725 726 727 728 729 730 731 732 733 734 735 736 737 738 739 740 741 742 743 744 745 746 747 748 749 750 751 752 753 754 755 756 757 758 759 760 761 762 763 764 765 766 767 768 769 770 771 772 773 774 775 776 777 778 779 780 781 782 783 784 785 786 787 788 789 790 791 792 793 794 795 796 797 798 799 800 801 802 803 804 805 806 807 808 809 810 811 812 813 814 815 816 817 818 819 820 821 822 823 824 825 826 827 investigations. On the other hand, it has been also shown that cultured RPE cells do express their specific markers during culture [48]. Our results could therefore also indicate that optimal culture conditions (e.g., coculture) can prolong the...…”
Section: Discussionsupporting
confidence: 50%
“…Additionally, we have included multiple RPE-specific markers (e.g., bestrophin) in our 708 709 710 711 712 713 714 715 716 717 718 719 720 721 722 723 724 725 726 727 728 729 730 731 732 733 734 735 736 737 738 739 740 741 742 743 744 745 746 747 748 749 750 751 752 753 754 755 756 757 758 759 760 761 762 763 764 765 766 767 768 769 770 771 772 773 774 775 776 777 778 779 780 781 782 783 784 785 786 787 788 789 790 791 792 793 794 795 796 797 798 799 800 801 802 803 804 805 806 807 808 809 810 811 812 813 814 815 816 817 818 819 820 821 822 823 824 825 826 827 investigations. On the other hand, it has been also shown that cultured RPE cells do express their specific markers during culture [48]. Our results could therefore also indicate that optimal culture conditions (e.g., coculture) can prolong the...…”
Section: Discussionsupporting
confidence: 50%
“…The results of the present study suggested that the wound-healing rate of the hAECT group was increased compared with that of the model and conventional treatment groups, and the healing time was reduced compared with that of the model and conventional treatment groups. The expression levels of TNF-α in the hAECT group on post-transplantation days 1, 3 and 7 were significantly elevated compared with those in the normal control, model and conventional treatment groups, indicating that the hAECs were able to differentiate and promote wound healing in the ischemic and hypoxic PU wounds (30,31); however, the level of TNF-α at day 7 was reduced compared with that in the model and conventional treatment groups, which further indicated that, in the late period of wound healing, the overexpression of TNF-α may lead to its disordered interaction with other cytokines, resulting in increased inflammatory damage (20).…”
Section: Discussionmentioning
confidence: 99%
“…We also performed immunostaining for RPE65 and pan-CK in the normal monkey retina specimen, and found that the neural retina was not stained with either marker, except for RPE65 staining in the photoreceptor layer where the red/green cone was present ( Figure 5 a,b). Traditionally, additional immunostaining should also be performed on other specific genes of RPE cells, such as cellular retinaldehyde-binding protein, vascular endothelial growth factor, CD68, and MERTK [ 22 , 23 ]. However, due to the limited amount of tissue we obtained during vitreous surgery, we were unable to perform the additional experiments in the two cases.…”
Section: Discussionmentioning
confidence: 99%